2020
DOI: 10.1089/hum.2019.174
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Phospho-Tau Gene Therapy for Chronic Traumatic Encephalopathy

Abstract: Chronic traumatic encephalopathy (CTE) is a progressive neurodegenerative disorder caused by repetitive trauma to the central nervous system (CNS) suffered by soldiers, contact sport athletes, and civilians following accident-related trauma. CTE is a CNS tauopathy, with trauma-induced inflammation leading to accumulation of hyperphosphorylated forms of the microtubule-binding protein Tau (pTau), resulting in neurofibrillary tangles and progressive loss of neurons. At present, there are no therapies to treat CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Some of the cerebral inflammatory mediators shown to be important in modulating neuroinflammation after TBI include TNF-α, INF-γ, IL-1β, IL-6, and IL-10 28 . Our study provides evidence that TXA administration may blunt the post-TBI cerebral cytokine release of IL-6, TNF-α and MCP-1 with a notable reduction in 30-day p-tau accumulation, which is a known marker of chronic traumatic encephalopathy 30 . Hiramoto et al 31 provided evidence that TXA and aprotonin administration ameliorated the aging-induced decline in memory and learning ability with notable reductions in cerebral IL-1β and TNF-α in TXA administered mice.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Some of the cerebral inflammatory mediators shown to be important in modulating neuroinflammation after TBI include TNF-α, INF-γ, IL-1β, IL-6, and IL-10 28 . Our study provides evidence that TXA administration may blunt the post-TBI cerebral cytokine release of IL-6, TNF-α and MCP-1 with a notable reduction in 30-day p-tau accumulation, which is a known marker of chronic traumatic encephalopathy 30 . Hiramoto et al 31 provided evidence that TXA and aprotonin administration ameliorated the aging-induced decline in memory and learning ability with notable reductions in cerebral IL-1β and TNF-α in TXA administered mice.…”
Section: Discussionmentioning
confidence: 54%
“…28 Our study provides evidence that TXA administration may blunt the post-TBI cerebral cytokine release of IL-6, TNF-α and MCP-1 with a notable reduction in 30-day p-tau accumulation, which is a known marker of chronic traumatic encephalopathy. 30 Hiramoto et al 31 provided evidence that TXA and aprotonin administration ameliorated the aginginduced decline in memory and learning ability with notable reductions in cerebral IL-1β and TNF-α in TXA administered mice. Although this study was not performed on TBI subjects, it did demonstrate that administration of antifibrinolytic medications may alter cerebral cytokine profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy by the use of monoclonal antibodies has also been studied in preclinical studies investigating tauopathies. Notably, a recent study demonstrated that the delivery of an adeno-associated virus (AAV) vector coding for an anti-pTau antibody reduced CNS pTau levels in rodent models of repeated traumatic brain injury [84]. An in-vitro study demonstrated that several tau antibodies successfully prevented neuronal tau uptake.…”
Section: Immunotherapymentioning
confidence: 99%
“…Expression of the gene should provide a sufficient level of antibodies that would prevent its accumulation. A research conducted on mice showed that delivery of AAVrh.10 expression vectors that encoded an antibody against tau protein to the hippocampus resulted in a significant decrease of the tau protein in central nervous system [38]. It is considered that inflammatory process plays an important role in the pathogenesis of CTE.…”
Section: Diagnostics Prevention and Treatmentmentioning
confidence: 99%